AN ANALYSIS OF PARTICIPIAL CONSTRUCTION AND ITS APPLICATION TO ENGLISH EDUCATION - Ito, Hayato (PEOPLE: International Journal of Social Sciences, 2017)
This study analyzes participial construction and aims to give an answer to why conjunctions like “when” and “while” are used in some participial construction by considering the iconic principle of sequential order, which is explained in Radden and Dirven (2007). In order to consider why conjunctions are added to participial constructions, we collect examples from COCA and analyze the differences between preposed and postposed participle clauses. With the analysis, we can argue that the order of clauses plays a role in showing the ground. i.e., the ground can either be expressed by adding the conjunction while, or by putting the clauses that express the ground in front. On the other hand, in the case of the participle clause with the conjunction when, we could not see such differences in the position; the clause with when can either be preposed or postposed. This might be attributable to the fact that when clearly shows simultaneity. Also, through the analysis, we will propose a better teaching method for the Japanese EFL learners.